Nuclear Transformation
XVI, 289 p.
Keywords: As part of its general rethinking of America's global strategy, the Bush Administration initiated a re-examination of America's nuclear doctrine that has generated considerable controversy with its focus on maintaining a reliance on nuclear weapons and potentially increasing willingness to use them. Here a group of leading strategic analysts examine the background to the re-evaluation, issues of implementation and potential implications internationally.